2003
DOI: 10.1186/gb-2003-4-4-r25
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide detection of segmental duplications and potential assembly errors in the human genome sequence

Abstract: Background: Previous studies have suggested that recent segmental duplications, which are often involved in chromosome rearrangements underlying genomic disease, account for some 5% of the human genome. We have developed rapid computational heuristics based on BLAST analysis to detect segmental duplications, as well as regions containing potential sequence misassignments in the human genome assemblies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
76
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(80 citation statements)
references
References 28 publications
(37 reference statements)
0
76
0
Order By: Relevance
“…Approximately 5% of the genome is low-copy-number repeat (LCR), also known as segmental duplications (15). An association between the locations of LCRs and constitutional copy-number polymorphisms is noted in refs.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 5% of the genome is low-copy-number repeat (LCR), also known as segmental duplications (15). An association between the locations of LCRs and constitutional copy-number polymorphisms is noted in refs.…”
Section: Resultsmentioning
confidence: 99%
“…The Human Genome Segmental Duplication Database (Cheung et al 2003) (http://projects.tcag.ca/humandup/) was used to check KIAA1549, BRAF, SRGAP3, and RAF1 for segmental duplications. The search for large regions of homology was conducted using BLASTN 2.2.22+ (Altschul et al 1997) (http://blast.ncbi.…”
Section: Bioinformatics Analysesmentioning
confidence: 99%
“…Moreover, our analysis of the entire human genome (using NCBI Build 31) revealed that chromosome 7 contained the largest amount of intrachromosomal duplication (23), which suggests that there could be other disease associations. To complete a more refined analysis of chromosome 7, we compared the CRA_TCAGchr7.v1 assembly with itself to search for all recent (>90% sequence identity) and large (>5 kb) intrachromosomal duplications.…”
Section: Chromosome 7 Functional and Structural Featuresmentioning
confidence: 99%